Steroid-Responsive Chronic Schizophreniform Syndrome in the Context of Mildly Increased Antithyroid Peroxidase Antibodies - Endres, Dominique; Perlov, Evgeniy; Riering, Anne Nicole; Maier, Viktoria; Stich, Oliver; Dersch, Rick; Venhoff, Nils; Erny, Daniel; Mader, Irina; Tebartz van Elst, Ludger (Frontiers in Psychiatry, 2017)
Background: Schizophreniform syndromes can be divided into primary forms from polygenic causes or secondary forms due to immunological, epileptiform, monogenic, or degenerative causes. Steroid-responsive encephalopathy associated with autoimmune thyroiditis (SREAT) is a secondary immunological form associated with increased thyroid antibodies, such as anti-thyroid peroxidase antibodies, and shows a good response to corticosteroids. Case presentation: We present the case of a 41-year-old woman suffering from a schizophreniform syndrome. Starting at the age of 35, she developed psychotic exacerbations with formal thought disorder, acoustic hallucinations, cenesthopathic experiences, and loss of ego boundaries. At the same time, she began to suffer from chronic sexual delusions and olfactory hallucinations, which did not respond to neuroleptic medication. Her levels of anti-thyroid peroxidase antibodies were slightly increased, and the blood–brain barrier was disturbed. An electroencephalogram (EEG) showed intermittent generalized slowing, and cerebral magnetic resonance imaging (cMRI) depicted mild temporolateral atrophy. High-dose corticosteroid treatment led to convincing improvement of attentional performance and the disappearance of delusions and olfactory hallucinations. Conclusion: SREAT can mimic typical symptoms of schizophreniform syndromes. The increased titer of anti-thyroid peroxidase antibodies in combination with the EEG slowing, blood–brain barrier dysfunction, and the cMRI alterations were the basis for suspecting an immunological cause in our patient. Chronic delusions, olfactory hallucinations, and cognitive deficits were successfully treated with corticosteroids. The occurrence of secondary immunological forms of schizophreniform syndromes demonstrates the need for innovative immunosuppressive treatment options.